Rapid Prototyping Design for the Community - Katoppo, Martin Luqman; Nugroho, Bambang T. A.; Hananto, Brian Alvin; Soenarjo, Hady; Liman, Sheena Y.; Onelim, Onieque; Anita, Michelle; Wibowo, Klarissa N.; Suripto, Chyntia A. (Jurnal Strategi Desain dan Inovasi Sosial, 2025)
Learning Express (LeX) Program is a program initiated by Singapore Polytechnic (SP) in cooperation with the School of Design, Universitas Pelita Harapan (SoD, UPH). LeX 2024 worked with 3 Ciakar’s, Tangerang communities to solve problems in their area: Darussalam School, Kebun Kandang Eco Farming, and Dodol Oyot SME. The research-design-action is conducted in 12 days using Design Thinking methods. The results would be rapid prototyping social innovation design for all the three communities.